ANALYSIS OF FINANCIAL PERFORMANCE AFFECTING MARKET SHARE OF SHARIA BANKING IN INDONESIA - Amalia Nasuha (Journal of Indonesian Applied Economics, 2020)
The trapped market share faced by sharia banking raises questions because the regulator's target is not achieved in projecting the market share. This study examines the effects of financial performance which includes the ROA, FDR, BOPO, NPF, and Conventional Commercial Bank Loans against the Sharia Banking market share in Indonesia. The data used are 108 monthly data from 2010 to 2018. The data was obtained from the publication of the Financial Services Authority of Islamic Banking Statistics and Indonesian Banking Statistics